2018
DOI: 10.1186/s12884-018-1975-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of the Women’s Development Army strategy implementation strength with household reproductive, maternal, newborn and child healthcare practices: a cross-sectional study in four regions of Ethiopia

Abstract: BackgroundTo address the shortfall in human resources for health, Ethiopia launched the Health Extension Program (HEP) in 2004, establishing a health post with two female health extension workers (HEWs) in every kebele (community). In 2011, the Women’s Development Army (WDA) strategy was added, using networks of neighboring women to increase the efficiency of HEWs in reaching every household, with one WDA team leader for every 30 households. Through the strategy, women in the community, in partnership with HEW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 29 publications
(19 reference statements)
5
44
0
Order By: Relevance
“…An approach that may initiate discussion on optimum birth interval is community mobilization through women's groups (e.g., Women's Development Army). The effectiveness of the Women's Development Army in improving maternal and child health services' outcomes has been documented elsewhere [49,50]. Furthermore, mass campaigns and health information dissemination, particularly in city and pastoralist communities, regarding optimum birth interval is required.…”
Section: Resultsmentioning
confidence: 99%
“…An approach that may initiate discussion on optimum birth interval is community mobilization through women's groups (e.g., Women's Development Army). The effectiveness of the Women's Development Army in improving maternal and child health services' outcomes has been documented elsewhere [49,50]. Furthermore, mass campaigns and health information dissemination, particularly in city and pastoralist communities, regarding optimum birth interval is required.…”
Section: Resultsmentioning
confidence: 99%
“…WDA is a network of one to five households represented by their team leaders. Based on geographic location of neighbourhoods, each WDA network is comprised of 25 to 30 households [24]. A list of 720 development teams was organized by the Daro Malo District Health Office [17].…”
Section: Study Design and Sampling Methodsmentioning
confidence: 99%
“…Pregnant women in the study zones were identified using the Antenatal Care log-book of the local Health Extension Workers [32]. Furthermore, we used leaders of the local Women Development Army groups to identify pregnant women not enrolled in the Antenatal Care [33]. All pregnant women (n = 468) in their second and third trimester living in the selected study zones, who met the study inclusion criteria were enrolled into the current study.…”
Section: Participants and Study Designmentioning
confidence: 99%